Considerations and Methodology to Determine R2R Manufacturing and Scaling of Electronic Devices on Flexible Stainless Steel Foil Substrates. (27th March 2017) - Chandra, Aditi; Takashima, Mao; Li, Joey; Beck, Patricia; Bruner, Scott; Tinsley, Dylan; Sreenivasan, Raghav; Kamath, Arvind
ABSTRACT: Stainless steel substrates enable a combination of low cost, flexibility, durability, high processing temperatures, and sub-100 um thickness making it well suited for sheet based and roll-to-roll processing. NFC (13.56 MHz) based circuits using high performance polysilicon TFTs on steel sheets have been manufactured using a hybrid printed process in a production environment. The process scheme utilizes a hybrid, additive materials approach encompassing low cost manufacturing steps such as slot die coating and screen printing of silicon and dopant inks to enable a high throughput, low cost, manufacturing flow. This paper describes the approach for migrating from a sheet-based hybrid process flow to a R2R-based process. A comparison of substrate choices and considerations for R2R process integration is presented. A sensitive electrical method for evaluating the feasibility of R2R-based process integration schemes and materials selection is presented. MIM capacitor leakage, TFT device characteristics, NFC circuit performance, and defect density considerations are shown as a function of steel substrate bending, down to a diameter of 0.75 inches. Electrical characteristics and optical inspections show no measurable change to insulator characteristics, demonstrating a high degree of flexibility and overall device and process capability for R2R processing.